Code-switching in relation to gender and social class: The case of an Egyptian TV series - Amin, Ayatallah Mohamed (AUC Knowledge Fountain, 2018)
This thesis analyzed stylized performance of Arabic-English code-switching (CS) and its interaction with gender, social class, and social networks in the context of the Egyptian comedy TV series Nelly and Sherihan. The theories of indexicality (Ochs, 1992; Silverstein ,1976), stance (Du Bois, 2007), and social networks (Milroy, J. & Milroy, L., 1985) were used to answer the research questions: 1) What is the social motivation for Arabic-English CS in relation to social class and gender specifically in the Egyptian TV series Nelly and Sherihan? 2) How do social networks as a variable affect Arabic-English CS of the main character in the Egyptian TV series Nelly and Sherihan? It was found that there is no common stance taken through CS that is typical of the high or the low social class or of a particular gender. Characters who belong to the low social class in Egypt are not portrayed in the TV series as constantly aggressive towards the high social class. They try to disassociate themselves from "localness" and align with the high social class using CS. However, they change their initial stance of alignment only when a salient aggressive disalignment by the high social class takes place. It was found that metalinguistic discourse about or containing CS instances between low and high social classes is always accompanied by a negative disalignment stance. Regarding gender in the TV series, it was concluded that, besides females, the Egyptian low social class males code-switch in an attempt to speak in a more prestigious way to resemble the higher social class and gain their approval. Regarding the frequency of CS in relation to change in social networks, it decreased when the main female character decides to affiliate with her "low social class" side of the family. Finally, the thesis identified a relationship between social networks, social class and stance. Change in social networks results in a change in stance where the direction of the change in the stance depends on the social class that constitutes the new social network.